2004
DOI: 10.1016/j.febslet.2004.03.094
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnogalacturonan lyase reveals a unique three‐domain modular structure for polysaccharide lyase family 4

Abstract: Rhamnogalacturonan lyase (RG-lyase) specifically recognizes and cleaves a-1,4 glycosidic bonds between L L -rhamnose and D D -galacturonic acids in the backbone of rhamno galacturonan-I, a major component of the plant cell wall polysaccharide, pectin. The three-dimensional structure of RGlyase from Aspergillus aculeatus has been determined to 1.5 A resolution representing the first known structure from polysaccharide lyase family 4 and of an enzyme with this catalytic specificity. The 508-amino acid polypeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…The other domains, especially domain III, were suggested to help form the substrate-binding groove. 4 Detailed studies have shown that the smallest substrate RGL4 can cleave is a deacetylated 12-residue oligomer, suggesting a binding site consisting of a minimum of 12 subsites in RGL4. 20 Cleavage occurs preferably four residues from Rha in the reducing end.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other domains, especially domain III, were suggested to help form the substrate-binding groove. 4 Detailed studies have shown that the smallest substrate RGL4 can cleave is a deacetylated 12-residue oligomer, suggesting a binding site consisting of a minimum of 12 subsites in RGL4. 20 Cleavage occurs preferably four residues from Rha in the reducing end.…”
Section: Introductionmentioning
confidence: 99%
“…The rhamnogalacturonan-degrading system of Aspergillus aculeatus has been well characterized over the years, and threedimensional structures of several enzymes have been elucidated, contributing toward the understanding of their function and mechanism. [4][5][6][7] Two main enzymes are involved in the breakdown of the RG-I backbone in A. aculeatus, a hydrolase and a lyase, while several other enzymes are necessary for the degradation of the RG-I side chains. RG hydrolase cleaves α-1,2 linkages between GalUA and Rha through a hydrolytic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Breakdown of rhamnogalacturonan is mainly mediated by two rhamnogalacturonan-degrading enzymes, rhamnogalacturonan hydrolase (RGaseA) and rhamnogalacturonan lyase (RGaseB). The rhamnogalacturonandegrading system of Aspergillus aculeatus has been well characterized, and three-dimensional structures of RGaseA and RGaseB have been elucidated, contributing toward the understanding of their structure-function relationship (Kofod et al, 1994, Mutter et al, 1994, Mutter et al, 1996a, Mutter et al, 1996b, Mutter et al, 1998, McDonough et al, 2004, Jensen et al, 2010. Furthermore, the usefulness of these enzymes in the processing of food has been confirmed.…”
Section: Introductionmentioning
confidence: 91%
“…This family displays a unique fold of three b-sandwich domains not found in other PL or GH families [21]. The structure of the rhamnogalacturonan lyase from Aspergillus aculeatus complexed with rhamnogalacturonan allowed identification of the active site and the location of À3 to +3 subsites (PDB code 3NJV, [22]).…”
Section: Metal-assisted Catalytic Mechanismmentioning
confidence: 99%